A New Evaluation Model for the Readiness and Maturity Level of Intelligent and Sustainable Supply Chain Management Based on Geometric Mean - Sercan Demir; Mehmet Akif Gündüz; Turan Paksoy (Journal of Transportation and Logistics)
Recently, companies have added smart and sustainable paradigms to their supply chain strategies as a result of globalization and increased global competition, increasing technological growth rate, diversity in customer demands, and increasing complexity in supply chain processes. Real-time information sharing among supply chain players and the effective coordination of each step of the chain are critical for efficient supply chain management. This is made possible by the transition from the traditional supply chain to the digital supply chain. The Fourth Industrial Revolution, also known as Industry 4.0, was coined for the first time in Germany in 2011. It is an innovative paradigm with the goal of intensely integrating technologies, such as information technologies, the Internet of Things, artificial intelligence, cloud computing technology, autonomous vehicles, robotic systems, sensor and automation networks, and virtual and augmented reality into production processes. However, for many companies, the adaptation of Industry 4.0 and the subsequent maturity period may present unexpected challenges. One of the most difficult challenges in establishing smart factories and implementing digital transformation is that Industry 4.0 competencies cannot be effectively applied to all operations simultaneously. In this context, quantitative measurement and evaluation of firms’ maturity levels following Industry 4.0 preparation and adaptation is critical for senior management. The goal of this study is to propose a model for measuring the maturity level of digital supply chains while considering smart and sustainable dimensions. We determined the extent to which each Industry 4.0 tool was compatible with the sustainability dimensions in the numerical example where the model was applied. For example, although additive manufacturing and augmented reality receive high scores in the economic dimension of sustainability, they receive lower scores in the environmental and social dimensions. Similarly, although horizontal and vertical systems integration has high levels of maturity in all three sustainability dimensions, artificial intelligence has an exceptionally low level of maturity.